Hubungan Mutu Pelayanan Kesehatan Gigi dan Mulut Menggunakan Aplikasi Klinisia dengan Kepuasan Pasien di UPTD Puskesmas Citangkil Kota Cilegon - Hanizar, Nizar (THERA-DENT (jurnal terapis gigi dan mulut), 2024)
Introduction: Dental and oral health problems are a significant public health problem at global, regional and national levels that can jeopardize the health of individuals and populations, although this is often not publicly acknowledged. Health care quality is the extent to which health care services provided to patients improve desired health outcomes. Purpose: To analyze the relationship between the quality of dental and oral health services using the Klinisia application with patient satisfaction at UPTD Citangkil Health Center, Cilegon City. Methods: This research uses a type of quantitative research, which is an analytical survey using cross-sectional study approach. Sampling was done using a minimum sample size technique using the solvin formula. The research subjects were all dental and oral care patients at UPTD Citangkil Health Center, Cilegon City. Results: The quality of dental and oral health service using the Klinisia application at UPTD Citangkil Health Center, Cilegon City show that the majority (88%) of patients are satisfied. The level of patient satisfaction at UPTD Citangkil Health Center, Cilegon City shows 64% with good results. Conclusion: There is arelationship between the quality of dental and oral health services using the klinisia application and pastient satisfaction at the UPTD Citangkil Health Centar, Cilegon City.